ANÁLISE DA DENSIDADE DA MADEIRA DE Pinus elliottii Engelm. POR MEIO DE RADIAÇÃO GAMA DE ACORDO COMAS DIREÇÕES ESTRUTURAIS (LONGITUDINALE RADIAL) EAIDADE DE C RESC IMENTO - Palermo, Gilmara Pires De Moura; Latorraca, João Vicente De Figueiredo; Rezende, Marcos Antônio De [UNESP]; Nascimento, Alexandre Miguel Do; Severo, Elias Taylor Durgante [UNESP]; Abreu, Heber Dos Santos (Instituto de Florestas da Universidade Federal Rural do Rio de Janeiro, 2023)
The adequated wood utilization depends on chemistry, physical and anatomical properties. Several biotic and abiotic factors can interfere, in higher or lower degree, in its properties and in its quality. This research had the objective to study the density variation, aiming to obtain knowledge towards its better application. The used wood samples were obtained from twelve Pinus elliottii trees of different growth ages. The results showed density variation in the longitudinal and radial direction and in function of the growth age. The density increased from pith to bark and with the growth age and decreased from bottom to upwards. Based on this variation, it was possible to distinguish regions where the density values are practically similar and regions where they differ, allowing thus, to classify the woods in terms of density and proposing its better application.

A melhor utilização da madeira depende de suas propriedades químicas, físicas e anatômicas. Diversos fatores bióticos e abióticos podem interferir em maior ou menor magnitude nas propriedades da mesma e conseqüentemente, em sua qualidade. Esta pesquisa teve como objetivo o estudo da variação da densidade da madeira, visando obter subsídios face sua melhor aplicação. O material empregado, constituiu-se de amostras de madeira de 12 árvores de Pinus elliottii com diferentes idades de crescimento. Os Resultados obtidos mostraram haver variação da densidade nos sentidos longitudinal e radial e em função da idade de crescimento. A densidade aumentou da medula para a casca e com a idade de crescimento e diminuiu da base para o topo. Baseado nesta variação, foi possível distinguir regiões onde os valores de densidades são praticamente idênticos e regiões onde eles diferem entre si, permitindo assim, classificar a madeira em termos de densidade e sugerir seu melhor emprego.
WOOD DENSITYANALYSIS OFPinus elliottii Engelm. BYGAMMARADIATION ACCORDINGTO STRUCTURALDIRECTIONS (LONGITUDINAL AND RADIAL)AND THE GROWTHAGE
Keywords: Pinus elliottii; wood density; gamma radiation; Pinus elliottii; densidade da madeira; radiação gama